(untitled) (Research, Society and Development, 2022)
The chronic venous insufficiency (CVI) is defined as alteration on the venous flow, caused by malfunction of the venous valves, obstruction of vases and weakness of the sural triceps muscle. The physical exercise is being studied as a form of treatment of this disease to be considered of low cost and easy access. Objective: The aim was to analyze the effects of different types of physical exercise in the venous hemodynamics, muscular function and in the quality of life of individuals with CVI ulcerated and non-ulcerated. Method: The articles were obtained by a research on six data bases. were included articles in which the exercise was a form of intervention in patients with CVI. Results: Were founded 2.297 clinical trials randomized and non-randomized, nine were included. These studies applied different protocols of exercise, that were an association of mobility, strength, force, and aerobic exercises. This association showed improvement in the different clinical conditions of the CVI, and a positive impact their quality of life. Conclusion: The physical exercise is benefic to patients with CVI, being able to reduce symptoms, increase quality of life and prevent the progression of the diseases, could reduce the cost to the health systems.